2016
DOI: 10.1007/s12031-016-0874-9
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH

Abstract: Complement-mediated inflammation plays a vital role in intracerebral hemorrhage (ICH), implicating pro-inflammatory factor interleukin-1beta (IL-1β) secretion. Brain samples and contralateral hemiencephalon were all collected and detected by Western blot. NLRP3 expression was located by dual immunofluorescence staining at 1, 3, and 5 days post-ICH. Brain water content was examined post-ICH. The neural deficit scores were evaluated by observers blindly. ILs were detected by ELISA. SiRNAs targeting NLRP3 (siNLRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 59 publications
2
33
0
Order By: Relevance
“…Mechanistic studies have shown an essential role for the NLRP3 inflammasome in brain injury and neuroinflammation after ICH. 9 11 The activation of NLRP3 inflammasome facilitates caspase-1 activation and IL-1β processing, leading to the amplification of the inflammatory response, which culminates in the expansion of perihematomal edema, and thereby exacerbating hemorrhagic brain injury. 9 11 As a small molecule, the NLRP3 inflammasome inhibitor, MCC950, was recently found to selectively inhibit NLRP3 inflammasome formation and reduce pyroptosis and IL-1β signaling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mechanistic studies have shown an essential role for the NLRP3 inflammasome in brain injury and neuroinflammation after ICH. 9 11 The activation of NLRP3 inflammasome facilitates caspase-1 activation and IL-1β processing, leading to the amplification of the inflammatory response, which culminates in the expansion of perihematomal edema, and thereby exacerbating hemorrhagic brain injury. 9 11 As a small molecule, the NLRP3 inflammasome inhibitor, MCC950, was recently found to selectively inhibit NLRP3 inflammasome formation and reduce pyroptosis and IL-1β signaling.…”
Section: Discussionmentioning
confidence: 99%
“… 9 11 The activation of NLRP3 inflammasome facilitates caspase-1 activation and IL-1β processing, leading to the amplification of the inflammatory response, which culminates in the expansion of perihematomal edema, and thereby exacerbating hemorrhagic brain injury. 9 11 As a small molecule, the NLRP3 inflammasome inhibitor, MCC950, was recently found to selectively inhibit NLRP3 inflammasome formation and reduce pyroptosis and IL-1β signaling. 17 In the present study, our results confirmed the ability of MCC950 to effectively inhibit the activation of NLRP3 inflammasome components and IL-1β production in experimental ICH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, in T-cells, a gene set enrichment analysis revealed a number of inflammasome-related genes to be upregulated following TCR/CD46 co-stimulation, including IL1-beta and NLRP3 [53]. In mice complement was a crucial inducer of Il-1β expression, and C3 −/− knock-out mice display a reduced inflammasome activation in microglial cells following brain inflammation [169].…”
Section: Intracellular Alarm Signalingmentioning
confidence: 99%